Gender based way in initial pre-professional training system of young football players - Suchilin, A.; Yakimovich, V.; Stolyarchuk, L. (BIO Web of Conferences, 2020)
The paper considers the gender-based way in initial pre-professional training of young football players (boys and girls) during their training in children`s and youth sport schools. The gender-based way and system analysis using allows us to get a handle on a system of initial training that includes a number of subsystems. All of them have a goal, objectives, program material and technology (methodology) for its implementation. Unlike the well-known studies, this one consists of using the same methodology in initial pre-professional training for joint football classes of boys and girls in age from 6 to 12 years old. This does not contradict their age characteristics and contributes to mutual enrichment in the development of technical and tactical techniques. From the age of 13, boys and girls begin to choose groups and football teams for in-depth pre-professional training to professional men`s and women`s football.